Increased D 1 dopamine receptor signaling in levodopa‐induced dyskinesia - Aubert, Incarnation; Guigoni, Céline; Håkansson, Kerstin; Li, Qin; Dovero, Sandra; Barthe, Nicole; Bioulac, Bernard H.; Gross, Christian E.; Fisone, Gilberto; Bloch, Bertrand; Bezard, Erwan (Annals of neurology, 2005)
Involuntary movements, or dyskinesia, represent a debilitating complication of levodopa therapy for Parkinson's disease. Although changes affecting D 1 and D 2 dopamine receptors have been studied in association with this condition, no causal relationship has yet been established. Taking advantage of a monkey brain bank constituted to study levodopa‐induced dyskinesia, we report changes affecting D 1 and D 2 dopamine receptors within the striatum of normal, parkinsonian, nondyskinetic levodopa‐treated parkinsonian, and dyskinetic levodopa‐treated parkinsonian animals. Whereas D 1 receptor expression itself is not related to dyskinesia, D 1 sensitivity per D 1 receptor measured by D 1 agonist‐induced [ 35 S]GTPγS binding is linearly related to dyskinesia. Moreover, the striata of dyskinetic animals show higher levels of cyclin‐dependent kinase 5 (Cdk5) and of the dopamine‐ and cAMP‐regulated phosphoprotein of 32kDa (DARPP‐32). Our data suggest that levodopa‐induced dyskinesia results from increased dopamine D 1 receptor–mediated transmission at the level of the direct pathway. Ann Neurol 2004